MAKING ACADEMIC BOOKS APPEALING TO STUDENTS - Abd Manan, Amerrudin; Wan Zakari, Wan Normeza (Journal of Human Capital Development (JHCD), 2012)
The use of humour in teaching and learning has perhaps mostly been limited to the teacher’s verbal communication during class times. Besides verbal communication, however, students also need to interact with instructional texts, for instance, course textbooks and academic books. Unfortunately, textbooks are usually not enjoyable to read because they are often written in a boring and serious manner. The questions that are seldom asked are, firstly, can writers inject a substantial number of jokes in students’ academic books so that they can be made engaging while delivering knowledge? Secondly, can writers distribute the jokes evenly throughout an academic book, and finally, can many types of jokes be incorporated in textbooks and academic books? Content analysis of Paraskos (1990) Economics book suggests that these questions do have positive answers. From a total of 178 pages, 80 cases of humorous expressions or jokes are found, and they are rather evenly spread throughout the book. The jokes can be (loosely) classified under fifteen categories based on their types. The brilliant strategy used by Paraskos to enliven students’ academic reading may transform both academicians’ approach in textbook writing and students’ attitude to academic reading. KEYWORDS: humour, academic books, economics, reading